An experimental test to separate the effects of male age and mating history on female mate choice. (7th October 2020) - Aich, Upama; Bonnet, Timothee; Fox, Rebecca J; Jennions, Michael D
Abstract: Should females prefer older males as mates? Male survival to old age might indicate the presence of fitness-enhancing genes that increase offspring fitness. However, many correlational studies show that mating with older males can lower female fecundity and even reduce offspring fitness due to epigenetic or germline mutation effects. One problem in quantifying female choice based on male age is that age is usually confounded with mating history. This begs a question: Do females choose males based on their age or their mating history? The answer requires an experimental approach, but few such studies exist. Here, we test if experimentally induced variation in the mating history of old and young males (12-week difference in postmaturity age) affects female choice in the eastern mosquitofish ( Gambusia holbrooki ). To vary mating history, adult males were either allowed to freely mate with females for 3 weeks or they only had visual contact with females. Immediately thereafter, we ran four-choice mating trials, using association time, to test the effects of male age and mating history (2 × 2 design) on male attractiveness. Females did not show a clear preference for males based on either characteristic. This was not due to a lack of female choice: females spent significantly more time with larger males. In addition, female choice was significantly repeatable across four trials: twice as a virgin and twice as a nonvirgin. Finally, female mating status (virgin or nonvirgin) did not affect her choice of mate, although virgin females spent significantly more time associating with test males. Abstract : As a female, would you mate with an old or young male? If you choose an older male, is this because he is more sexually experienced or because of his actual age? We experimentally disentangled the effects of male age and mating history on female choice in the eastern mosquitofish. Despite females being consistent in their choice of certain mates, specifically larger males, they did not prefer males based on their age or mating history.